The Uniformity and Its Impact on Reliability for 3 300 V IGBT Chip in Traction Application - LIU Guo-you; LUO Hai-hui; LIU Ke-an; HUANG Jian-wei; ZHANG Quan (机车电传动)
In order to meet the special requirements of traction application, 3 300 V IGBT was supposed to have the excellent gate control capability, the lower on-state voltage drop and the wider safe operating area, an intensive study had been made on chip processes of 3 300 V IGBT. Some measurements had been taken on the process control and the critical processes improvement, so as to greatly improve the characteristics of gate driving, voltage blocking, on-state performance, and safe operating area. Therefor, the reliability has been significantly enhanced.